Peran Guru Fiqh Menerapkan Model Pembelajaran Drill (Pengulangan) Untuk Meningkatkan Pengamalan Ibadah Shalat Pada Siswa Kelas Vii Mts Swasta Yaspen Muslim Pematang Tengah - Amalia Octaviani; M. Yusuf Abdullah; Nurmisda Ramayani (Jurnal Berbasis Sosial, 2022)
Identification of problems found at the research location, namely: The application of the DRILL learning model in teaching and learning activities in the field of Jurisprudence had been implemented but before the covid 19 pandemic. However, currently the implementation of the DRILL model is hampered by restrictions on learning activities, namely Distance Learning. This research has a problem formulation, namely: How is the role of the teacher in applying the DRILL learning model (repetition) in learning and teaching activities for students in class VII MTs. Private Yaspen Muslim Central Pematang?. How to practice prayer in class VII MTs. Private Yaspen Muslim Central Pematang?. What is the role of the teacher in applying the DRILL Learning model (repetition) in improving the practice of praying in class VII MTs. Private Yaspen Muslim Central Pematang?. The conclusions of the implementation of this research are: The role of the Fiqh study teacher in applying the DRILL (Repetition) learning model to improve the practice of praying for the seventh grade students of Islamic Islamic Junior High School Yaspen Muslim Pematang Tengah has been running optimally and the implementation of the DRILL (Repetition) learning model has been running effectively to improving the practice of praying for students is evidenced by the existence of a repetition program as an effort to familiarize students with praying both in the madrasa environment and at home.